2007
DOI: 10.1515/bc.2007.043
|View full text |Cite
|
Sign up to set email alerts
|

N.BspD6I DNA nickase strongly stimulates template-independent synthesis of non-palindromic repetitive DNA by Bst DNA polymerase

Abstract: Highly efficient DNA synthesis without template and primer DNAs occurs when N.BspD6I DNA nickase is added to a reaction mixture containing deoxynucleoside triphosphates and the large fragment of Bst DNA polymerase. Over a period of 2 h, virtually all the deoxynucleoside triphosphates (dNTPs) become incorporated into DNA. Inactivation of N.BspD6I nickase by heating inhibits DNA synthesis. Optimal N.BspD6I activity is required to achieve high yields of synthesized DNA. Electron microscopy data revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 18 publications
5
59
0
Order By: Relevance
“…We have previously shown that Bst DNA poly merase, similarly to many thermophilic polymerases, can synthesize DNA in the absence of template DNA and primer [5]. Therefore, the effect of SSB proteins on template/primer independent DNA synthesis per formed by Bst DNA polymerase in the absence of nicking endonuclease was studied first.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that Bst DNA poly merase, similarly to many thermophilic polymerases, can synthesize DNA in the absence of template DNA and primer [5]. Therefore, the effect of SSB proteins on template/primer independent DNA synthesis per formed by Bst DNA polymerase in the absence of nicking endonuclease was studied first.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of these timepoints was due to the fact that intense synthesis of high molecular weight DNA occurs mostly during the first hour of the reaction (at the DNA polymerase: nicking endonuclease ratio used in the present work). The synthesis is accompanied by DNA hydrolysis by nickase, since the DNA synthesized contains tandem sequences of nicking endonuclease recognition sites [5] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, a brief period of specific amplification was followed by a rapid increase in nonspecific amplification. Thermophilic polymerases are known to be able to initiate template-independent de novo DNA synthesis and amplification [57,58], particularly in the presence of endonucleases [34,59,60]. We chose Sequenase 2.0 as the best polymerase candidate for further investigation because it has a far superior synthesis rate and processivity [55] compared to Klenow exo- and does not exhibit the nonspecific background amplification observed in most thermophilic polymerases.…”
Section: Discussionmentioning
confidence: 99%